Toward a Revolution in Australian Children’s Data and Privacy - Leaver, Tama; Mannell, Kate; Duffy, Gavin; Bunn, Anna; Ng, Rebecca; Zhao, Xinyu (2023)
This panel combines four papers which focus in different ways on the question of children’s data and privacy in the Australian context. All four are framed with children’s right to privacy as a core concern, consistent with the UN Convention on the Rights of the Child as updated via the General Comment 25 on Child Rights in the Digital Environment. We examine four arenas where children’s data is either extracted or occluded in ways that make it more difficult, if not impossible, for parents, carers and others to make informed choices about the data of very young children. As children begin to articulate their own ideas and privacy preferences, these studies highlight different understandings of privacy, and of trust in both people and technologies. The panel papers are titled: ‘Where Does Children’s Data Go? Mapping the Data Broker Industry’; ‘Data and Privacy as a Social Relation’; ‘Developing a Holistic Framework for Analysing Privacy Policies – A Child’s Rights and Data Justice Perspective’ and ‘Unboxing Data and Privacy Via Young Children’s Wearables’. Collectively, these papers can be read as arguing that we need nothing less than a revolution in the way children and responsible adults are informed about the way children’s data is generated, captured, stored, and owned, as well as explicitly regulating who can profit from children’s data, in which circumstances, and how transparent these processes must be.